Summer Houses, Ruin, Demolition and Rehabilitation , Modern Architecture heritage between 1950 and 1960 in Portugal - Tiago Freitas (Joelho)
From the decades 1930/1940 in Portugal, begins the search for a new architectural model of holiday house derived from the chalet. From the late 1950s and according to Ana Tostões[1], begins a widespread acceptance of modern architecture by an elite bourgeoisie which will develop new resorts in Portugal. According to Rui Ramos [2] the urbanization along the beaches from Ofir in the North to Rodízio in the South, reveals this new way of modern living. These houses have resisted as built heritage from the decades of the 1940 till now. Some have not been able to avoid demolition; others are in a state of decay and abandoned ruin. It is urgent to avoid bad interventions that adulterate there main architectural characteristics or even the ruin and consequent demolishing in order of touristic investments of greater value. House Aiola was located in Arrábida, work of unquestionable modern taste, made use of prefabrication systems. The use of new materials, such as plywood and wood panels makes this house an authentic modern laboratory. The internal organization of the house in perfect communion with the outside is very fluid. According to Rui Ramos[3], the house reveals an unconditional adoption of modern, being able to innovate on the constraints imposed on it. The quality of this house and the uniqueness of his work transform this house one of the most radically modern examples built in Portugal, yet virtually unknown and demolished. The José Soares House in Ofir, of architects Cassiano Barbosa and Arménio Losa, was built in the year of 1950.  This unknown work of the modern Portuguese architects is located in the summer resort of Ofir, where other important summer houses were built predominately between the decades of 1940 and 1970. This house experiments the new modern movement concepts as the use of ramps, new materials as fibre cement roofing or the clear distribution of sleeping and living areas in two blocks. At the same time it questions vernacular architecture by the use of apparent granite stone walls, the use of decorative tiles or wooden joinery. Nowadays the house is abandoned for decades and is coming to an advanced state of ruin. Modern Portuguese architecture has to be enlightened as of great value, so that owners and general public get aware of its heritage, before bigger mistakes are made.